WITTGENSTEIN, LANGUAGE AND INFORMATION Back to the Rough Ground - BLAIR, DAVID; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
This book is an extension of the discussions presented in Blair's 1990 book "Language and Representation in Information Retrieval", which was selected as the "Best Information Science Book of the Year" by the American Society for Information Science (ASIS). That work stated that the Philosophy of Language had the best theory for understanding meaning in language, and within the Philosophy of Language, the work of philosopher Ludwig Wittgenstein was found to be most perceptive. The success of that book provided an incentive to look more deeply into Wittgenstein's philosophy of language, and how it can help us to understand how to represent the intellectual content of information. This is what the current title does, and by using this theory it creates a firm foundation for future Information Retrieval research. The work consists of four related parts. Firstly, a brief overview of Wittgenstein's philosophy of language and its relevance to information systems. Secondly, a detailed explanation of Wittgenstein's late philosophy of language and mind. Thirdly, an extended discussion of the relevance of his philosophy to understanding some of the problems inherent in information systems, especially those systems which rely on retrieval based on some representation of the intellectual content of that information. And, fourthly, a series of detailed footnotes which cite the sources of the numerous quotations and provide some discussion of the related issues that the text inspires.
Keywords: COMPUTER SCIENCE; LINGUISTICS -- PHILOSOPHY; PHILOSOPHY OF MIND; INFORMATION STORAGE AND RETRIEVAL SYSTEMS; TEXT PROCESSING (COMPUTER SCIENCE; LIBRARY SCIENCE; COMPUTER SCIENCE; COMPUTER SCIENCE, GENERAL; PHILOSOPHY OF LANGUAGE; INFORMATION STORAGE AND RETRIEVAL; LIBRARY SCIENCE; DOCUMENT PREPARATION AND TEXT PROCESSING; PHILOSOPHY OF MIND